DESKRIPSI KBK UNTUK MENYELESAIKAN MASALAH PECAHAN MELALUI GAYA KOGNITIF SISWA: DESCRIPTION OF CRITICAL THINKING ABILITIES TO SOLVE FRACTION PROBLEMS THROUGH STUDENTS' COGNITIVE STYLES - Pemu, Nasrullah; Layn, Muhamad Ruslan (Universitas Muhammadiyah Sorong, 2024)
This study aims to describe students' critical thinking ability (CTA) in solving mathematical problems on the topic of fractions based on cognitive styles. The research was conducted using a descriptive qualitative method, involving two students from SMPN 2 Takalar as subjects. The instruments used were the GEFT test, a critical thinking ability test, and interview guidelines. The results of the study showed that overall, FI students demonstrated better abilities in analysis, evaluation, and inference compared to FD students. Although both had equal abilities in interpretation, FI students stood out in overall critical thinking ability based on the given indicators. Additionally, FD students were less capable of making conjectures, formulating, and providing reasons for solutions. However, they performed well in manipulating mathematics. Moreover, FD students were unable to draw conclusions and check the validity of arguments. On the other hand, FI students were able to make conjectures, manipulate mathematics, draw conclusions from statements, and check the validity of arguments. Cognitive style is important in critical thinking activities for learning fractions; therefore, students should be given learning opportunities to not remain static in their current cognitive style.